Synergism of red and blue light in the control of Arabidopsis gene expression and development - Sellaro, Romina Vanesa (2009)
The synergism between red and blue light in the control of plant growth and development requires the coaction of the red light photoreceptor phytochrome B (phyB) and the blue light and UV-A receptor cryptochromes (cry). Here, we describe the mechanism of the coaction of these photoreceptors in controlling both development and physiology. In seedlings grown under red light, a transient supplement with blue light induced persistent changes in the transcriptome and growth patterns. Blue light enhanced the expression of the transcription factors LONG HYPOCOTYL 5 (HY5) and HOMOLOG OF HY5 (HYH) and of SUPPRESSOR OF PHYA 1 (SPA1) and SPA4. HY5 and HYH enhanced phyB signaling output beyond the duration of the blue light signal, and, contrary to their known role as repressors of phyA signaling, SPA1 and SPA4 also enhanced phyB signaling. These observations demonstrate that the mechanism of synergism involves the promotion by cry of positive regulators of phyB signaling. The persistence of the light-derived signal into the night commits the seedling to a morphogenetic and physiological program consistent with a photosynthetic lifestyle.